(-)-Epicatechin reduces adiposity in male offspring of obese rats. (10th June 2019) - De los Santos, Sergio; Reyes-Castro, Luis Antonio; Coral-Vázquez, Ramón Mauricio; Méndez, Juan Pablo; Leal-García, Marcela; Zambrano, Elena; Canto, Patricia
Abstract: Objective: To determine whether (-)-epicatechin (Epi) could decrease visceral adipose tissue and improve the metabolic profile of male offspring rats, after maternal obesity was induced by a high-fat diet (HFD). Design: Maternal obesity in albino Wistar rats was induced with a HFD, whereas male offspring were fed with chow diet throughout the study. Eight male offspring per group, from different litters, were randomly assigned to the experimental or to the control groups. In the experimental group, Epi was administered at a dose of 1 mg/kg of body weight to the male offspring twice daily for two weeks, beginning at postnatal day (PND). Main measures: Weight of visceral adipose tissue, adipocyte size, and several metabolic parameters. Results: Epi administration in the male offspring induced a significant decrease in the amount of visceral fat (11.61 g less, P < 0.05) and in the size of adipose cells (28% smaller, P < 0.01). Besides, Epi was able to decrease insulin, leptin, and Homeostasis Model Assessment -Insulin Resistance (HOMA-IR) (P < 0.05), as well as triglycerides, when the experimental group was compared to the untreated male offspring of obese rats (P < 0.01). Conclusions: Epi administration can reverse the negative effects that maternal obesity has on the male offspring. This could be because Epi reduces the amount of visceral fat and improves metabolic profile.